PENGENALAN KEWIRAUSAHAAN DAN TAHAPAN DESAIN THINKING PENGEMBANGAN PRODUK PADA SANTRI - Ahmad; Rafeal JP; Kenneth A (Jurnal Serina Abdimas, 2025)
This activity aims to improve students' understanding of entrepreneurship and product design through a real-life example-based approach that can be used as business inspiration. This training is conducted face-to-face in a room provided by the partner, using a lecture method equipped with case studies and design examples. This method was chosen to provide direct experience for participants in understanding the concept of entrepreneurship and product development based on design thinking. The enthusiasm of the participants for the material presented was very high, showing their interest in understanding and applying the concept of entrepreneurship. The results of the questionnaire showed that 80% of participants considered this training very useful in developing entrepreneurial knowledge. Understanding of the concept of product design increased significantly, with an understanding level reaching 89.5%, while the ability to create product ideas reached 97.4%. In addition, 84.2% of participants stated that they had a better understanding of the concept of product design after participating in this training. The design thinking approach applied in this training also helps participants identify market needs and develop problem-based business ideas that are relevant to the community. This training provides important insights into business innovation strategies, starting from market analysis to product testing through a systematic approach. It is expected that this program can be a basis for students in developing sustainable businesses and contributing to a stronger entrepreneurial ecosystem. To optimize the impact of the program, further development is needed such as business mentoring and increasing access to entrepreneurial resources. ABSTRAK Kegiatan ini bertujuan untuk meningkatkan pemahaman santri tentang kewirausahaan dan desain produk melalui pendekatan berbasis contoh nyata yang dapat dijadikan inspirasi bisnis. Pelatihan ini dilakukan secara tatap muka di ruang yang telah disediakan oleh mitra, menggunakan metode ceramah yang dilengkapi dengan studi kasus dan contoh desain. Metode ini dipilih untuk memberikan pengalaman langsung bagi peserta dalam memahami konsep kewirausahaan dan pengembangan produk berbasis design thinking. Antusiasme peserta terhadap materi yang disampaikan sangat tinggi, menunjukkan ketertarikan mereka dalam memahami dan menerapkan konsep kewirausahaan. Hasil kuisioner menunjukkan bahwa 80% peserta menilai pelatihan ini sangat bermanfaat dalam mengembangkan pengetahuan kewirausahaan. Pemahaman terhadap konsep desain produk meningkat secara signifikan, dengan tingkat pemahaman yang mencapai 89,5%, sedangkan kemampuan dalam menciptakan ide produk mencapai 97,4%. Selain itu, 84,2% peserta menyatakan bahwa mereka memiliki pemahaman yang lebih baik tentang konsep desain produk setelah mengikuti pelatihan ini. Pendekatan design thinking yang diterapkan dalam pelatihan ini juga membantu peserta dalam mengidentifikasi kebutuhan pasar dan mengembangkan ide bisnis berbasis masalah yang relevan dengan masyarakat. Pelatihan ini memberikan wawasan penting terkait strategi inovasi bisnis, dimulai dari analisis pasar hingga pengujian produk melalui pendekatan sistematis. Diharapkan program ini dapat menjadi dasar bagi santri dalam mengembangkan bisnis yang berkelanjutan dan berkontribusi pada ekosistem kewirausahaan yang lebih kuat. Untuk mengoptimalkan dampak program, perlu dilakukan pengembangan lebih lanjut seperti pendampingan bisnis dan peningkatan akses terhadap sumber daya kewirausahaan.